Knowledge, Attitude and Practice of Community Pharmacists Toward Non-pharmaceutical Products in Saudi Arabia - Almaghaslah, Dalia (Frontiers in Public Health, 2022)
Abstract Introduction: Community pharmacy is a rapidly changing sector in Saudi Arabia. Customers visit local community pharmacies for a variety of reasons including disease-related advice, buying OTC medication, cosmetic products and re-filling a prescription for a chronic illness. The current study was conducted to fill the gap in the literature regarding community pharmacists’ knowledge, attitude and practice towards nonpharmaceutical products. Methods: The study used a cross-sectional design. A total of 211 community pharmacists working in the Asir region, Saudi Arabia were included. The questionnaire was adopted from a previous study with the same purpose. Results: Products sold in community pharmacies were mainly pharmaceutical products (69.7%) compared to 30.3% non-pharmaceutical products. The most commonly sold non-pharmaceutical products were mother and baby products (26%) and skin care products (19%). Pharmacists showed good mean knowledge (3.96 out of 5), mean positive attitude (3.79 out of 5) and mean positive practice (3.32 out of 5). Conclusion: Community pharmacists showed considerable knowledge pertaining to non-pharmaceutical products. Respondents demonstrated positive attitudes towards the non-pharmaceutical products and were interested in expanding their knowledge on the topic through continuing education. Additionally, they showed social accountability by assuming responsibility for providing patient counselling on non-pharmaceutical products.